Barriers and enablers for supply chain integration in prefabricated elements manufacturing in New Zealand - Nishadi Sooriyamudalige (International Journal of Construction Supply Chain Management, 2020)
The attention on prefabricated modules and components is resurging in the New Zealand residential construction industry. This is driven by its relative benefits and technological advancements. However inspite of this attention, there has not been commensurate understanding of its manufacturing supply chain and the enhancement of their performance. Similarly, there has been little research considering the supply chain and supply chain integration in module/component manufacturing in residential construction in New Zealand. Therefore, this paper presents a comprehensive overview of the modular manufacturing process and the barriers and enablers for supply chain integration in module manufacturing. The identified barriers are discussed with their relevant enablers. Information for the study investigation was collected through twelve semi-structured face to face interviews with prefabrication experts. The information obtained was analysed using content analysis that enabled the development of a framework that illustrates barriers and enablers for supply chain integration. Ad-hoc relationships, poor planning and scheduling, transporting of volumetric modules and information sharing are a few significant barriers in the manufacturing process of modular bathroom pods and wall panels in New Zealand. The proposed framework provides a guide for the wall panel and bathroom pods manufacturing companies to improve integration across their entire manufacturing process.